1984
DOI: 10.1111/j.1600-051x.1984.tb00904.x
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of untreated periodontal disease

Abstract: 1016 textile workers were examined during a baseline study in 1969/70. A follow-up examination in 1979/80 identified 82 subjects who had not been treated for periodontal disease in the intervening period. There were 39 male and 43 female subjects; the average age at the initial examination was 27.0 years. There was an average tooth loss of 2.5 (SEM 0.6) teeth per subject over the 10-year period. While periodontal disease was significantly related to oral hygiene at the outset, neither factor was significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
33
1
1

Year Published

1985
1985
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(41 citation statements)
references
References 17 publications
6
33
1
1
Order By: Relevance
“…Table 3 illustrates the variation in risk level and periodontal disease severity within our study population, which is consistent with previous reports 1,10,11 Table 4. illustrates the variation in tooth loss within our study population, which is consistent with previous reports 3–8 . We compared our study population to the populations of seven studies of prevalence and tooth loss.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Table 3 illustrates the variation in risk level and periodontal disease severity within our study population, which is consistent with previous reports 1,10,11 Table 4. illustrates the variation in tooth loss within our study population, which is consistent with previous reports 3–8 . We compared our study population to the populations of seven studies of prevalence and tooth loss.…”
Section: Discussionsupporting
confidence: 87%
“…We compared our study population to the populations of seven studies of prevalence and tooth loss. These studies 1,3‐8 used no more than five levels of severity, and risk was not used at all. Therefore, our method of combining severity with risk increased the categories for comparison nine‐fold.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The maintenance subjects lost 0.12 teeth/subject/year, whereas the rate for the prophylaxis group was 0.02 teeth/subject/year. The rate of tooth loss in our periodontal maintenance group is comparable to other reports 9–11 of annual tooth loss rates for periodontitis patients under maintenance and lower than the rates described for untreated populations 12,13 . Our data also indicated that the periodontal condition of the extracted teeth was the primary cause of tooth loss in the maintenance group.…”
Section: Discussionsupporting
confidence: 84%
“…7 However, it is also clear from previously published papers that periodontal therapy without compliance with a maintenance regime is of doubtful value. 8 How many patients do not complete their periodontal treatment plan, or fail to attend for their SPC programme? Most reports show low levels of compliance with maintenance therapy, with results varying between 11 and 45%.…”
Section: Verifiable Cpd Papermentioning
confidence: 99%